Tributação mineral no Brasil: uma abordagem comparativa - Paulo Honório de Castro Júnior (2022)
In this research, we aim to verify, from the 1988 Constitution and international experience, what is the tax and financial regime on mining in Brazil. It is intended to propose suggestions for its improvement. There are, therefore, two questions that this dissertation intends to answer: a) What is the fiscal regime (tax and financial) for mining in Brazil, defined by the 1988 Constitution? b) Is it possible to verify successful examples of mining taxation in foreign experience? If so, to what extent can they be applied to the Brazilian legal system? The hypothesis, for item (a), is that there seems to be a constitutional tax and financial regime for mining in the text of the 1988 Constitution. There is evidence that there is a mechanism that articulates and directs the constitutional rules related to mining towards the achievement of constitutional purposes. For example, the rule of art. 20, § 1, of the Constitution links royalties with a model of fiscal or patrimonial federalism, as well as with a tax regime that admits the levy of ICMS on minerals and IOF on gold, under certain conditions. For item (b), the hypothesis is that there are successful examples of mineral taxation in the international experience.